2021
DOI: 10.1097/jom.0000000000002359
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With the Work Productivity of Japanese Working Pregnant Women

Abstract: Objectives: Working pregnant women experience physical and psychosocial changes, which are associated with two aspects of work productivity: presenteeism and absenteeism. We examined the factors that affect these two aspects. Methods: This cross-sectional study was conducted in April to May 2019 through an online survey. Participants were 450 working women who were pregnant for the first time. Results: Occupational stress (job overload sb: 0.14, suitable jobs sb: 0.16); physical conditions, such as pregnancy c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Furthermore, it is possible that the use of social systems also had an effect, although it was not examined in this survey. It has been reported that job performance during pregnancy is lower in early pregnancy, increases toward the middle of pregnancy, and then decreases toward the end of pregnancy [ 14 , 35 ]. Therefore, The period of pregnancy should be taken into account even if the woman is pregnant.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Furthermore, it is possible that the use of social systems also had an effect, although it was not examined in this survey. It has been reported that job performance during pregnancy is lower in early pregnancy, increases toward the middle of pregnancy, and then decreases toward the end of pregnancy [ 14 , 35 ]. Therefore, The period of pregnancy should be taken into account even if the woman is pregnant.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Occupational stress during pregnancy is associated with an increased risk of preterm birth, small for gestational age, and low birth weight 16) . A study examining the correlates of presenteeism and absenteeism in working pregnant women reported that occupational stress, such as work overload and job suitability, was significantly associated with presenteeism 17) . Meanwhile, a study examining the association between occupational stress and fertility outcomes found that women who perceived their jobs as more demanding were significantly less likely to become pregnant, and women in shift work were less likely to become pregnant 18) .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, being pregnant was significantly associated with physical stress reactions 20) . Although previous studies 16,17) have investigated the effects of occupational stress on pregnant women, they have not investigated how pregnancy itself affects occupational stress. Furthermore, some studies 20) did not adjust for the number of children or measure the impact of pregnancy alone.…”
Section: Introductionmentioning
confidence: 99%